Interannual variability of the Atlantic North Equatorial Undercurrent and its impact on oxygen - Burmeister, Kristin; Lübbecke, Joke F.; Brandt, Peter; Duteil, Olaf (Journal of Geophysical Research: Oceans, 2019)
The North Equatorial Undercurrent (NEUC) has been suggested to act as an important oxygen supply route towards the oxygen minimum zone in the Eastern Tropical North Atlantic. Observational estimates of the mean NEUC strength are uncertain due to the presence of elevated mesoscale activities, and models have difficulties in simulating a realistic NEUC. Here we investigate the interannual variability of the NEUC and its impact onto oxygen based on the output of a high‐resolution ocean general circulation model (OGCM) and contrast the results with an unique data set of 21 ship sections along 23° W and a conceptual model. We find that the interannual variability of the NEUC in the OGCM is related to the Atlantic Meridional Mode (AMM) with a stronger and more northward NEUC during negative AMM phases. Discrepancies between OGCM and observations suggest a different role of the NEUC in setting the regional oxygen distribution. In the model a stronger NEUC is associated with a weaker oxygen supply towards the east. We attribute this to a too strong recirculation between the NEUC and the northern branch of the South Equatorial Current (nSEC) in the OGCM. Idealized experiments with the conceptual model support the idea that the impact of NEUC variability on oxygen depends on the source water pathway. A strengthening of the NEUC supplied out of the western boundary acts to increase oxygen levels within the NEUC. A strengthening of the recirculations between NEUC and the nSEC results in a reduction of oxygen levels within the NEUC.